Description of nymphal instars and adult female of Kermes vermilio Planchon (Hemiptera, Coccoidea, Kermesidae), with a synopsis of the European and Mediterranean species - Pellizzari, Giuseppina; Porcelli, Francesco; Convertini, Stefano; Marotta, Salvatore (Zootaxa, 2012)
The morphology of the 1st-instar, 2nd-instar male and female, 3rd-instar female and adult female of Kermes vermilio Planchon (Hemiptera Coccoidea Kermesidae) are described and illustrated; micrographs of some morphological details are also provided. An identification key to instars and a table showing the present status of knowledge on the morphology of European and Mediterranean Kermes instars is included.